Ad-valorem equivalents of NTMs in ASEAN - Olivier Cadot; Lili Yan Ing (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
To obtain country specific estimates of ad-valorem equivalent (AVE) of Non-Tariff Measures (NTMs), we propose a a new that relies on the estimation of bilateral trade flows on two-way panels (product X importer X exporter) at the HS 2-digit level with importer, exporter and product fixed effects and interaction terms between NTM variables and full vector of country-specific characters. Our results show that AVEs for TBT measures on manufactured products, both for ASEAN countries and the sample as a whole, at 4.5 percent and 5 percent, respectively. As for SPS measures on agriculture and food products, tariff AVEsfor ASEAN countries and the sample as a whole 6.5 percent and 6.7 percent, respectively. However, it should be noted that AVEs can mean very different things depending on whether they have a counterpart in the correction of a market failure. This depends on the technical capabilities of domestic regulatory agencies.
Keywords: 330; Non-tariff measures